Recycling of lignocellulosics filled polypropylene composites. I. Analysis of thermal properties, morphology, and amount of free radicals. Issue 12 (2nd December 2014) - Paukszta, Dominik; Markiewicz, Ewa; Ostrowski, Adam; Doczekalska, Beata; Brzyska, Magdalena; Szostak, Marek; Borysiak, Sławomir
ABSTRACT Composites of isotactic polypropylene filled with comminuted rapeseed straw are studied. Improvement in interfacial adhesion is achieved by chemical modification of the lignocellulose filler. Composites were subjected to recycling by extrusion. The effect of multiple recycling of the composites on the process of nucleation and crystallization of polypropylene matrix, surface topography, and free radical generation was checked. On the basis of differential scanning calorimetry data, a significant influence of the recycling on nucleation activity of the lignocellulose filler was evidenced. A relation between the filler particle size and multiple recycling was established by observations under a polarization microscope, while scanning electron microscope analyses confirmed the positive effect of chemical modification of rapeseed straw on the interfacial adhesion. The composite structure changes forced by multiple recycling are discussed in the context of free radical generation. Concentration of free radicals in the rapeseed straw samples and composites was measured by the electron paramagnetic resonance spectroscopy to show that it was higher in the systems subjected to multiple recycling. Interestingly, the composites after multiple recycling showing elevated concentration of free radicals are also characterized by higher nucleation activity. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41693.